Adaptive Supervision Model: Facing the Dynamics of Education in the 21st Century - Dwi Utari; Sudadi Sudadi (Departement of Mathematics Education, 2023)
The Adaptive Supervision Model is a personalised and technology-based approach to educational supervision that emphasises responsiveness and flexibility to the unique needs of the educational context. It encourages teacher empowerment and leadership, contextualised support, and a balance between feedback and coaching. This model shifts the supervision paradigm from traditional supervision to an essential tool for improving the quality of learning and teaching in a changing educational environment. This research discusses the concept of adaptive supervision, an approach that adapts to the unique needs and dynamics of learning. The research method used is a qualitative method with a descriptive approach. Through this approach, supervision is not only preventive and corrective, but also a responsive mechanism to changes in learning demands, technological developments and individual needs. With the concept and implementation of the Adaptive Supervision Model, this article opens a discussion on how this adaptive approach can shape the future of educational supervision that is effective, responsive and empowering. Through an analysis of the model's characteristics, it also identifies implementation challenges, such as a lack of technological readiness, a paradigm shift in the role of supervisors, and difficulties in personalising services. In response to these challenges, the article offers strategies, including competency training, effective communication, development of guidelines, teacher participation in decision-making, strengthening collaborative culture, continuous monitoring and evaluation, psychosocial support, and collaboration with external parties. By applying these strategies, it is hoped that the implementation of the Adaptive Supervision Model can be successful and contribute significantly to the development of education in the future.